Cellulase activities and finishing effects - Paulo, Artur Cavaco (1996)
Cellulase enzymes are usually characterized by evaluation of their activities towards different forms of cellulose and their derivatives. For textile applications, it was suggested thet the comparative evaluation should also include the measurement of the activities in tests that simulate the large scale treatments with different degrees of mechanical agitation. Comparisons were made between three cellulase mixtures with know compositions and two commercial cellulase by the proposed methodologies. The relations between cellulase activities of these enzyme mixturea and finishing effects obtained for different processes with various degree of mechanical agitation are shown.